Double-walled microcapsules for cementitious materials, and methods of making and using the same
By utilizing the double-walled microcapsule structure, the synergistic effect of the components in the core and wall solves the problems of poor mechanical properties and interfacial compatibility of microcapsules in cement-based materials, achieving efficient crack repair and cost control.
Patent Information
- Application Number
- CN202511163773.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-08-20
AI Technical Summary
Existing cement-based material microcapsules suffer from poor mechanical properties, poor interfacial compatibility, and high cost. In particular, organic or organic-inorganic composite microcapsules have problems such as poor heat resistance, lack of chemical bonding at the interface, and high cost when used in cement-based materials.
The microcapsule structure with double walls is adopted. The core is composed of hydrated aluminum sulfate, sodium bentonite and calcium oxide expansion agent. The capsule wall is composed of a first capsule wall composed of water glass, metakaolin and water and a second capsule wall composed of chemically stable ultrafine calcium carbonate. The multi-component synergistic effect achieves efficient self-repair of cracks.
It improves the interfacial compatibility and mechanical properties of cement-based materials, ensures the long-term effectiveness of microcapsules, reduces costs, and achieves effective crack repair and improved mechanical properties.
Smart Images

Figure CN120717716B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a double-walled microcapsule for cement-based materials, its preparation method, and its application. Background Technology
[0002] Cement-based materials, as a core foundational material in modern construction, are inherently brittle, making them prone to microcracks under external stress or temperature changes. These cracks not only represent structural defects but also trigger stress concentration effects, significantly weakening the structure's mechanical load-bearing capacity and long-term durability. Of particular concern is the secondary damage caused by crack propagation, such as steel corrosion and freeze-thaw cycles, which seriously threaten the safe service life of building structures and constitute significant engineering hazards.
[0003] Traditional physical repair techniques rely on manual inspection and localized intervention, which have significant limitations: First, accessibility restrictions in high-altitude and concealed areas create repair blind spots; second, processes such as grooving and grouting easily cause secondary structural damage, forming a vicious cycle of "repair-damage"; third, delayed repair is unable to suppress the dynamic propagation of cracks, and the repair effect exhibits significant spatiotemporal discrete characteristics. Against this backdrop, self-healing material systems have attracted significant attention from the academic community due to their intelligent "sensing-response-repair" characteristics. This technology, through pre-placed repair agent carriers, achieves targeted repair at the moment crack initiation, not only maintaining the continuity of material mechanical properties but also blocking the penetration channels of environmental corrosive media, thus improving the reliability of the structure throughout its entire life cycle from the source of damage.
[0004] As the core carrier of self-healing systems, the performance of the capsule wall material directly determines the repair efficacy of microcapsule technology. Current research mainly focuses on organic or organic-inorganic composite capsule walls, but three major technical bottlenecks are prevalent: ① In terms of mechanical properties, organic capsule walls such as urea-formaldehyde resin have poor heat resistance and low mechanical strength, making them difficult to adapt to the thermodynamic environment of cement hydration; ② In terms of interfacial compatibility, organic materials such as ethyl cellulose lack chemical bonding with cement-based materials, easily forming interfacial defects and affecting overall performance; ③ From an engineering applicability perspective, the nano-silica modification process suffers from particle agglomeration and high costs. Therefore, developing all-inorganic microcapsules with high strength, excellent interfacial adhesion, good thermal stability, and controllable cost has become a key research direction for overcoming the bottlenecks in the engineering application of self-healing materials.
[0005] Therefore, there is a need to provide an improved technical solution that addresses the shortcomings of the existing technology. Summary of the Invention
[0006] The purpose of this invention is to provide a double-walled microcapsule for cement-based materials, its preparation method and application, so as to help solve or improve at least one of the problems of poor mechanical properties, poor interfacial compatibility and high cost of organic or organic-inorganic composite microcapsules in the prior art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a double-walled microcapsule for cement-based materials, comprising: a core, the core comprising the following components: hydrated aluminum sulfate, sodium bentonite, and calcium oxide-based expanding agent; and a wall comprising a first wall and a second wall; the first wall comprising water glass, metakaolin, and water; the second wall comprising calcium carbonate; and the first wall disposed between the core and the second wall.
[0008] Preferably, by weight, the core comprises: 10-30 parts of hydrated aluminum sulfate, 20-40 parts of sodium bentonite, and 50-70 parts of calcium oxide-based expanding agent.
[0009] Preferably, the fineness of the hydrated aluminum sulfate is 80-100 mesh and the purity is >99wt%; the fineness of the sodium-based bentonite is 600-800 mesh and the total mass content of SiO2 and Al2O3 is ≥85wt%; the particle size of the calcium oxide expanding agent is 200-300 mesh and the effective CaO content is ≥60wt%.
[0010] Preferably, by mass, the first capsule wall comprises: 40-50 parts water glass, 15-20 parts metakaolin, and 30-45 parts water.
[0011] Preferably, the mass ratio of water glass to metakaolin is (2.2-2.7):1.
[0012] Preferably, the water glass has a modulus of 2.8-3.2 and a concentration of 30wt%-35wt%. The metakaolin has a specific surface area of 11000-13000 m². 2 / kg, with a total mass content of SiO2 and Al2O3 ≥97wt%.
[0013] Preferably, the calcium carbonate has a fineness of 6000-8000 mesh.
[0014] Preferably, the mass ratio of the first capsule wall to the second capsule wall is 4:1; the mass ratio of the core of the double-walled microcapsule for cement-based materials to the sum of the masses of the first and second capsule walls is 3:1.
[0015] The present invention also provides a method for preparing a double-walled microcapsule for cement-based materials, which adopts the following technical solution: The method for preparing a double-walled microcapsule for cement-based materials as described above includes the following steps: (1) uniformly mixing the hydrated aluminum sulfate, sodium bentonite and calcium oxide expansion agent, granulating and drying to obtain a core; (2) uniformly mixing the water glass, metakaolin and water to obtain a suspension; (3) spraying the suspension onto the surface of the core to obtain a microcapsule containing a first core wall; (4) adhering calcium carbonate powder as a second core wall to the surface of the microcapsule containing the first core wall obtained in step (3), thereby obtaining the double-walled microcapsule for cement-based materials.
[0016] The present invention also provides the application of the double-walled microcapsules for cement-based materials as described above, which adopts the following technical solution: the double-walled microcapsules for cement-based materials as described above are used to prepare self-healing cement-based materials.
[0017] Beneficial effects:
[0018] The double-walled microcapsules of the present invention for cement-based materials have good interfacial compatibility with cement-based materials, good mechanical properties (do not cause a significant reduction in the strength of cement-based materials), and good repair effect on cracks in cement-based materials.
[0019] Furthermore, the raw materials used in this invention (e.g., hydrated aluminum sulfate, sodium bentonite, calcium oxide-based expanding agents, etc.) are all green materials, which meet the requirements of green building and sustainable development.
[0020] The role of the double-walled microcapsules for cement-based materials in this invention:
[0021] (1) Synergistic effect of multiple materials in the core: First, the calcium oxide-based expansive agent in the core acts as a fast-reacting and early-filling component. When it comes into contact with H2O entering the crack, it reacts rapidly to generate calcium hydroxide, resulting in significant solid volume expansion, which can quickly and physically fill the crack. Subsequently, the calcium hydroxide reacts with CO2 entering from the outside to form dense calcium carbonate, further improving the filling effect of the crack area. Second, the sodium bentonite in the core acts as a water-absorbing, sealing, and environmental regulation component. It absorbs water and expands rapidly upon contact with water, forming a gel-like substance at the crack, further sealing the crack and blocking water transport. At the same time, its slow water release characteristic can provide a continuous moist microenvironment for the subsequent chemical reaction of calcium oxide and aluminum sulfate, replenishing the repair material. Furthermore, in the alkaline environment provided by the calcium oxide-based expansive agent and cement clinker hydration, the active SiO2 and Al2O3 between the sodium bentonite layers gradually dissolve and participate in the reaction to generate CSH gel, further improving the density of the crack area. Third, the hydrated aluminum sulfate in the core acts as a strength-enhancing component. It hydrolyzes upon contact with water to generate Al 3+ and SO4 2-These ions further react with the already formed calcium hydroxide to form ettringite (…). The slightly expanded needle-like ettringite crystals further compact and fill the crack areas, improving local mechanical properties.
[0022] (2) Inorganic double-walled structure: The first wall consists of water glass, metakaolin, and water. The reaction between the three is a typical alkali-activated reaction: after water glass dissolves in water, it first undergoes dissociation and hydrolysis, providing an alkaline environment and silicate ions (SiO3). 2- This stimulates metakaolin to release active aluminate (Al(OH)4) ions. - ) and silicate (SiO3) 2- The ions eventually form an aluminosilicate gel network structure, which gradually hardens to form a continuous membrane that encapsulates the core, preventing premature release. The second capsule wall is made of chemically stable ultrafine calcium carbonate, which offers several advantages as the second capsule wall for the double-walled microcapsules of cement-based materials in this invention: Firstly, it avoids direct contact between the first capsule wall and the hardened cement paste, preventing premature activation of the first capsule wall by the highly alkaline environment of the cement paste, thus ensuring the long-term effectiveness of the microcapsules. Secondly, this ultrafine calcium carbonate has good compatibility and strong adhesion with the hardened cement paste; it makes the interface transition zone between the double-walled microcapsules and the hardened cement paste more compact, allowing them to work together under external force, thereby reducing the potential negative impact of the double-walled microcapsules on the mechanical properties of the cement-based materials to some extent. Attached Figure Description
[0023] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein:
[0024] Figure 1 The image shows a physical picture of the double-walled microcapsules for cement-based materials of the present invention (a small amount of methyl violet colorant is added to the capsule wall composed of the first and second capsule walls to facilitate observation of the capsule walls).
[0025] Figure 2 Thermogravimetric curves of the core and wall of the double-walled microcapsule for cement-based materials in Example 1 are shown.
[0026] Figure 3 The image shows a cross-sectional view of a mortar specimen containing double-walled microcapsules for cement-based materials from Example 1, after standard curing for 28 days; where (b) is a partial enlarged view of (a).
[0027] Figure 4 The figures show the test results of the effect of the water glass content ratio on the double-walled microcapsules of the present invention for cement-based materials; wherein, (a) is a physical image of the double-walled self-healing microcapsules prepared when the mass ratio of metakaolin to water glass is 5:3, (b) is a physical image of the first capsule wall suspension prepared when the mass ratio of metakaolin to water glass is 1:4, (c) is a physical image of the double-walled self-healing microcapsules prepared when the mass ratio of metakaolin to water glass is 1:4, and (d) is a physical image of the double-walled self-healing microcapsules prepared when the water glass content ratio is appropriate (the mass parts of water glass and metakaolin are 40-50 parts and 15-20 parts, respectively).
[0028] Figure 5 The figure shows the test results of the effect of the ratio of the mass of the core to the sum of the masses of the first and second capsule walls on the double-walled microcapsules for cement-based materials of the present invention; wherein, (a) is a cross-sectional view of the double-walled self-healing microcapsule prepared when the ratio of the mass of the core to the sum of the masses of the first and second capsule walls is 4:1, (b) is a cross-sectional view of the double-walled self-healing microcapsule prepared when the ratio of the mass of the core to the sum of the masses of the first and second capsule walls is 2:1, and (c) is a cross-sectional view of the double-walled self-healing microcapsule prepared when the ratio of the mass of the core to the sum of the masses of the first and second capsule walls is 3:1.
[0029] Figure 6 The graph shows the compressive strength test results of mortar specimens with double-walled microcapsules incorporated in Example 1 for cement-based materials and blank mortar specimens. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0031] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0032] This invention addresses at least one of the problems of poor mechanical properties, poor interfacial compatibility, and high cost of existing organic or organic-inorganic composite microcapsules by providing a double-walled microcapsule for cement-based materials.
[0033] The double-walled microcapsule for cement-based materials according to embodiments of the present invention includes: a core, comprising the following components: hydrated aluminum sulfate, sodium bentonite, and calcium oxide-based expanding agent; and a wall, comprising a first wall and a second wall; the first wall comprises water glass, metakaolin, and water; the second wall comprises calcium carbonate; and the first wall is disposed between the core and the second wall.
[0034] The core of the double-walled microcapsule for cement-based materials of the present invention is composed of hydrated aluminum sulfate, sodium bentonite and calcium oxide expansive agent. It achieves efficient self-repair of cracks through the synergistic effect of multiple components, as follows: (1) The calcium oxide expansive agent in the core acts as a fast reaction and early filling component. When it comes into contact with H2O entering the crack, it reacts rapidly to generate calcium hydroxide, which expands significantly in solid volume and can quickly physically fill the crack. Subsequently, the calcium hydroxide reacts with CO2 entering from the outside to form dense calcium carbonate, which further improves the filling effect of the crack area; (2) The sodium bentonite in the core acts as a water absorbent The sealing and environmental regulation components absorb water and expand rapidly upon contact with water, forming a gel-like substance at the crack (see formula (1)), further sealing the crack and blocking water transmission; at the same time, its slow water release characteristics can provide a continuous moist microenvironment for the subsequent chemical reaction of calcium oxide and aluminum sulfate, replenishing the repair material; furthermore, under the alkaline environment provided by calcium oxide expansion agents and cement clinker hydration, the active SiO2 and Al2O3 between the sodium bentonite layers gradually dissolve, participate in the reaction to generate CSH gel, further improving the density of the crack area; (3) The hydrated aluminum sulfate in the core is a strength-enhancing component, which hydrolyzes upon contact with water to generate Al 3+ and SO4 2- These ions further react with the already formed calcium hydroxide to form ettringite (…). (See equation (2)). The micro-expanded needle-shaped ettringite crystals further compact and fill the crack area, improving the local mechanical properties.
[0035] (1)
[0036] (2)
[0037] The first capsule wall consists of water glass, metakaolin, and water. The reaction between these three components is a typical alkali-activated reaction: after the water glass dissolves in water, it first undergoes dissociation and hydrolysis, providing an alkaline environment and silicate ions (SiO3). 2- This stimulates metakaolin to release active aluminate (Al(OH)4) ions. - ) and silicate (SiO3) 2- The ions eventually form a silicate gel network structure, which gradually hardens to form a continuous membrane that encapsulates the core and prevents it from being released prematurely.
[0038] The second capsule wall is made of chemically stable ultrafine calcium carbonate, which has multiple advantages as the capsule wall of the double-walled microcapsules for cement-based materials of this invention: Firstly, it isolates the first capsule wall from direct contact with the hardened cement-based slurry, preventing premature activation of the first capsule wall by the highly alkaline environment of the hardened cement-based slurry, thus ensuring the long-term effectiveness of the microcapsules. Secondly, this ultrafine calcium carbonate has good compatibility with the hardened cement-based slurry and strong adhesion; it makes the interface transition zone between the double-walled microcapsules and the hardened cement-based slurry of this invention more compact, allowing the double-walled microcapsules and the hardened cement-based slurry to work together under external force, thereby reducing the potential negative impact of the incorporation of the double-walled microcapsules on the mechanical properties of the cement-based material to a certain extent.
[0039] In a preferred embodiment of the double-walled microcapsule for cement-based materials of the present invention, the core comprises, by weight parts: 10-30 parts of hydrated aluminum sulfate (e.g., 10, 14, 16, 20, 24, or 30 parts), 20-40 parts of sodium bentonite (e.g., 20, 23, 27, 30, 33, or 40 parts), and 50-70 parts of calcium oxide-based expanding agent (e.g., 50, 53, 57, 60, 63, or 70 parts). If the proportion of hydrated aluminum sulfate is too high, on the one hand, too much ettringite will be formed early, leading to concentrated crystallization stress, which is detrimental to crack healing; on the other hand, too high a content of hydrated aluminum sulfate may consume too many OH⁻ ions, lowering the local pH of the core, thereby inhibiting calcium hydroxide formation and further weakening the continuous formation of ettringite. If the proportion of hydrated aluminum sulfate is too low, Al at the crack... 3+ and SO4 2- Insufficient ion concentration leads to a small amount of ettringite formation, resulting in low bonding strength of the restoration and poor restoration effect.
[0040] If the proportion of sodium-based bentonite is too high, the total amount of effective remediation material will decrease, affecting the remediation effect; moreover, sodium-based bentonite will adsorb more free water, hindering the reaction of calcium oxide-based expansion agents and Al. 3+ SO4 2- The dissolution and diffusion of sodium bentonite reduce the repair efficiency; if the proportion of sodium bentonite is too small, on the one hand, the water retention is too small to maintain the moist environment required for continuous repair; on the other hand, it cannot provide more SiO2 to participate in the reaction to generate CSH gel, thus reducing the bonding strength of the repaired area.
[0041] If the proportion of calcium oxide-based expansive agent is too high, too much calcium hydroxide will be generated from the hydration of calcium oxide, resulting in excessive solid volume expansion stress in the early stage. This will cause microcracks to form in the hardened slurry of the cement-based material around the repair area, which will negatively affect the repair effect. If the proportion of calcium oxide-based expansive agent is too low, the expansion amount will be insufficient and the cracks will not be effectively sealed. In addition, it will also cause the pH value to be too low, the aluminum sulfate reaction efficiency to decrease, and the amount of ettringite generated will also decrease.
[0042] A physical image of the double-walled microcapsules for cement-based materials of the present invention is shown below. Figure 1 As shown (a small amount of methyl violet colorimetric reagent was added to the capsule wall (including the first capsule wall and the second capsule wall) for easier observation).
[0043] In a preferred embodiment of the double-walled microcapsules for cement-based materials of the present invention, the fineness of hydrated aluminum sulfate is 80-100 mesh and the purity is >99wt%; the fineness of sodium bentonite is 600-800 mesh and the total mass content of SiO2 and Al2O3 is ≥85wt%; the particle size of calcium oxide expansive is 200-300 mesh and the effective CaO content is ≥60wt%.
[0044] In a preferred embodiment of the double-walled microcapsule for cement-based materials of the present invention, the first capsule wall comprises, by weight parts: 40-50 parts of water glass (e.g., 40, 42, 44, 46, 48, or 50 parts), 15-20 parts of metakaolin (e.g., 15, 16, 17, 18, 19, or 20 parts), and 30-45 parts of water (e.g., 30, 35, 40, or 45 parts). A physical image of the double-walled microcapsule for cement-based materials prepared according to the above proportions is shown below. Figure 4 As shown in (d); if the proportion of water glass is too small (the mass ratio of kaolin to water glass is 5:3), the overall viscosity will be significantly higher, making it difficult to disperse and spray the first capsule wall into a film (the actual image of the prepared double-capsule microcapsules for cement-based materials is shown in Figure 1). Figure 4 (a) As shown in the figure); if the proportion of water glass is too large (the mass ratio of kaolin to water glass is 1:4), the viscosity of the first capsule wall suspension obtained by mixing the raw materials of the first capsule wall will decrease significantly (e.g. Figure 4 (b) As shown, although the first capsule wall suspension is easy to form a film, its application in the fabrication of the double-capsule microcapsules for cement-based materials of the present invention will cause the double-capsule microcapsules for cement-based materials of the present invention to be prone to cracking and premature release of the capsule core (as shown in the figure). Figure 4 (as shown in (c)).
[0045] Preferably, the mass ratio of water glass to metakaolin is (2.2-2.7):1 (e.g., 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1 or 2.7:1).
[0046] Preferably, the modulus of the water glass is 2.8-3.2 (e.g., 2.8, 2.9, 3.0, 3.1 or 3.2), and the concentration is 30wt%-35wt% (e.g., 30wt%, 31wt%, 32wt%, 33wt%, 34wt% or 35wt%).
[0047] In a preferred embodiment of the double-walled microcapsules for cement-based materials of the present invention, the specific surface area of metakaolin is 11000-13000 m². 2 / kg, with a total mass content of SiO2 and Al2O3 ≥97wt%. If the specific surface area of metakaolin is too large, it will adsorb more free water, resulting in excessively high viscosity of the slurry in the first capsule wall. This makes it difficult to form a continuous and uniform first capsule wall during the spray coating process, potentially leading to a wide particle size distribution, poor molding quality, or even failure to form an effective first capsule wall in the prepared double-capsule microcapsules for cement-based materials. Conversely, if the specific surface area of metakaolin is too small, the release rate of active SiO2 and Al2O3 is slow, resulting in a large amount of unreacted metakaolin remaining in the first capsule wall. This makes the first capsule wall prone to damage and unable to effectively protect the capsule core.
[0048] In a preferred embodiment of the double-walled microcapsule for cement-based materials of the present invention, the calcium carbonate has a fineness of 6000-8000 mesh.
[0049] Preferably, the mass ratio of the first capsule wall to the second capsule wall is 4:1; the mass ratio of the core mass to the sum of the masses of the first and second capsule walls in the double-capsule microcapsules used for cement-based materials is 3:1 (a cross-sectional view of the double-capsule self-healing microcapsules prepared when the mass ratio of the core mass to the sum of the masses of the first and second capsule walls is 3:1 is shown in the figure). Figure 5 (c) shows that, to facilitate observation of the capsule wall, a small amount of methyl violet colorant is added to the capsule wall (including the first capsule wall and the second capsule wall); the thickness of the capsule wall of the double-capsule microcapsule for cement-based materials of the present invention is approximately 200 μm. If the proportion of the second capsule wall is too small, it will be difficult to effectively isolate the first capsule wall, which may cause an early reaction between the first capsule wall and the hardened slurry of the cement-based material, reducing its long-term stability. If the proportion of the second capsule wall is too large, although it may help improve the overall strength of the double-capsule microcapsule for cement-based materials to some extent, when microcracks occur in the cement-based material, the stress at the crack tip may not be sufficient to rupture the double-capsule microcapsule for cement-based materials of the present invention, making it difficult for the capsule core to be released in time, reducing the repair effect on the cracks. If the ratio of the mass of the capsule core to the total mass of the first and second capsule walls is too large, the capsule wall becomes thinner or even cannot completely enclose the capsule core, causing the capsule core to be released prematurely, affecting the repair effect (e.g., Figure 5 As shown in (a); Figure 5(a) The ratio of the mass of the core to the total mass of the first and second capsule walls in the corresponding double-walled microcapsules for cement-based materials of the present invention is 4:1, and the thickness of the capsule walls is 0-100 μm; since the colors of the capsule walls and cores are similar, a small amount of methyl violet dye is added to the capsule walls for easy differentiation); if the ratio of the mass of the core to the sum of the masses of the first and second capsule walls is too small, the content of effective substances for crack repair actually loaded in a unit of the double-walled microcapsules for cement-based materials of the present invention will decrease, thereby affecting the repair effect (e.g. Figure 5 As shown in (b); Figure 5 (b) The ratio of the mass of the core to the sum of the masses of the first and second capsule walls in the corresponding double-walled microcapsules for cement-based materials is 2:1, and the thickness of the capsule wall is 300-400 μm; since the colors of the capsule wall and the core are similar, a small amount of methyl violet dye is added to the capsule wall for easy differentiation.
[0050] The present invention also proposes a method for preparing double-walled microcapsules for cement-based materials. The method for preparing double-walled microcapsules for cement-based materials according to the present invention includes the following steps: (1) uniformly mixing hydrated aluminum sulfate, sodium bentonite and calcium oxide expansion agent, granulating (preferably, granulation can be carried out in a spherical granulator or a disc granulator) and drying to obtain a core; (2) uniformly mixing water glass, metakaolin and water to obtain a suspension; (3) spraying the suspension obtained in step (2) onto the surface of the core (preferably, this step can be carried out in a granulator) to obtain microcapsules containing a first core wall; (4) adhering calcium carbonate powder to the surface of the microcapsules containing the first core wall obtained in step (3) as a second core wall to obtain double-walled microcapsules for cement-based materials.
[0051] In a preferred embodiment of the method for preparing double-walled microcapsules for cement-based materials according to the present invention, the particle size of the double-walled microcapsules for cement-based materials is 1-3 mm.
[0052] Preferably, step (1) further includes the step of spraying anhydrous ethanol into the granulator; the mass of the sprayed anhydrous ethanol is 20%-24% of the total mass of the capsule core (e.g., 20%, 21%, 22%, 23% or 24%).
[0053] The present invention also proposes the application of the double-walled microcapsules for cement-based materials as described above. The application of the double-walled microcapsules for cement-based materials in the embodiments of the present invention is as follows: the above-mentioned double-walled microcapsules for cement-based materials are used to prepare self-healing cement-based materials (that is, in the process of preparing cement-based materials, the double-walled microcapsules for cement-based materials of the present invention are added, so that when cracks occur, the double-walled microcapsules for cement-based materials of the present invention can play a role in repairing the cracks).
[0054] The following detailed description, through specific embodiments, illustrates the double-walled microcapsules for cement-based materials of the present invention, their preparation method, and their applications.
[0055] Unless otherwise specified, all raw materials used in the following examples are commercially available. The main raw materials are as follows: aluminum sulfate octahydrate with a fineness of 80-100 mesh and a purity greater than 99wt%; sodium bentonite with a fineness of 600-800 mesh and a total SiO2 and Al2O3 content of not less than 85wt%; calcium oxide-based expanding agent with a particle size of 200-300 mesh and an effective CaO content of not less than 60wt%; water glass with a modulus of 3.2 and a solution concentration of 35wt%; and metakaolin with a specific surface area of 11000-13000 m². 2 / kg; the fineness of calcium carbonate is 6000-8000 mesh; the silica sol has a silica content of 30.37wt%, pH 9.5, and an average particle size of 10.7nm, and was purchased from Hebei Aorui Environmental Protection Technology Co., Ltd.
[0056] The chemical compositions (mass percentage) of calcium oxide-based expanding agents, sodium-based bentonite, and metakaolin are shown in Table 1 below:
[0057] Table 1. Chemical composition of calcium oxide-based expanding agents, sodium bentonite, and metakaolin.
[0058]
[0059] Example 1
[0060] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0061] The core, by weight, comprises: 10 parts aluminum sulfate octahydrate, 20 parts sodium bentonite, and 70 parts calcium oxide-based expanding agent;
[0062] The capsule wall includes a first capsule wall and a second capsule wall;
[0063] The first capsule wall, by mass fraction, comprises: 40 parts water glass, 16 parts metakaolin, and 44 parts water;
[0064] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0065] The method for preparing double-walled microcapsules for cement-based materials in this embodiment includes the following steps:
[0066] (1) Weigh each component according to the stated proportions for later use;
[0067] (2) Mix 10 parts of aluminum sulfate octadechydrate, 20 parts of sodium bentonite and 70 parts of calcium oxide expansion agent in a mixer at 120±2r / min for 10min. Then, use disc granulation technology to make the core agglomerate into balls by spraying anhydrous ethanol (the amount of anhydrous ethanol is 22%±2% of the total mass of the core) in a granulator (speed is 40±5r / min). Dry at 50±2℃ for 2h.
[0068] (3) Mix 40 parts water glass, 16 parts metakaolin and 44 parts water, and disperse by ultrasonication for 5 minutes to obtain the first capsule wall suspension;
[0069] (4) The capsule cores prepared in step (2) are sieved (square mesh sieves with apertures of 1 mm and 3 mm) to obtain capsule cores with a particle size range of 1-3 mm; then, the first capsule wall suspension obtained in step (3) is sprayed onto the surface of the capsule cores using a spheroidizing granulator (80 parts by mass of the first capsule wall suspension and 300 parts by mass of the capsule core) to obtain microcapsules containing the first capsule wall;
[0070] (5) 20 parts of calcium carbonate powder are adhered to the surface of the microcapsule containing the first capsule wall (380 parts by mass) obtained by step (4) as the second capsule wall. After drying at 60±2℃ for 12h, the microcapsule is sieved to obtain the double capsule wall microcapsule for cement-based materials of this embodiment with a particle size of 1-3mm.
[0071] Example 2
[0072] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0073] The core, by weight, comprises: 10 parts aluminum sulfate octahydrate, 40 parts sodium bentonite, and 50 parts calcium oxide-based expanding agent;
[0074] The capsule wall includes a first capsule wall and a second capsule wall;
[0075] The first capsule wall, by mass, comprises: 50 parts water glass, 20 parts metakaolin, and 30 parts water;
[0076] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0077] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0078] Example 3
[0079] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0080] The core, by weight, comprises: 30 parts aluminum sulfate octahydrate, 20 parts sodium bentonite, and 50 parts calcium oxide-based expanding agent;
[0081] The capsule wall includes a first capsule wall and a second capsule wall;
[0082] The first capsule wall, by mass, comprises: 50 parts water glass, 18.5 parts metakaolin, and 31.5 parts water;
[0083] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0084] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0085] Example 4
[0086] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0087] The core, by weight, comprises: 10 parts aluminum sulfate octahydrate, 30 parts sodium bentonite, and 60 parts calcium oxide-based expanding agent;
[0088] The capsule wall includes a first capsule wall and a second capsule wall;
[0089] The first capsule wall, by mass fraction, comprises: 40 parts water glass, 15 parts metakaolin, and 45 parts water;
[0090] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0091] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0092] Example 5
[0093] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0094] The core, by weight, comprises: 20 parts aluminum sulfate octahydrate, 20 parts sodium bentonite, and 60 parts calcium oxide-based expanding agent;
[0095] The capsule wall includes a first capsule wall and a second capsule wall;
[0096] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0097] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0098] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0099] Example 6
[0100] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0101] The core, by weight, comprises: 20 parts aluminum sulfate octahydrate, 30 parts sodium bentonite, and 50 parts calcium oxide-based expanding agent;
[0102] The capsule wall includes a first capsule wall and a second capsule wall;
[0103] The first capsule wall, by mass fraction, comprises: 42 parts water glass, 16 parts metakaolin, and 42 parts water;
[0104] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0105] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0106] Example 7
[0107] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0108] The core, by weight, comprises: 16 parts aluminum sulfate octahydrate, 27 parts sodium bentonite, and 57 parts calcium oxide-based expanding agent;
[0109] The capsule wall includes a first capsule wall and a second capsule wall;
[0110] The first capsule wall, by mass fraction, comprises: 42 parts water glass, 19 parts metakaolin, and 39 parts water;
[0111] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0112] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0113] Example 8
[0114] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0115] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 23 parts sodium bentonite, and 63 parts calcium oxide-based expanding agent;
[0116] The capsule wall includes a first capsule wall and a second capsule wall;
[0117] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0118] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0119] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0120] Example 9
[0121] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0122] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 33 parts sodium bentonite, and 53 parts calcium oxide-based expanding agent;
[0123] The capsule wall includes a first capsule wall and a second capsule wall;
[0124] The first capsule wall, by mass fraction, comprises: 49 parts water glass, 19 parts metakaolin, and 32 parts water;
[0125] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0126] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0127] Example 10
[0128] The double-walled microcapsule for cement-based materials in this embodiment includes:
[0129] The core, by weight, comprises: 24 parts aluminum sulfate octahydrate, 23 parts sodium bentonite, and 53 parts calcium oxide-based expanding agent;
[0130] The capsule wall includes a first capsule wall and a second capsule wall;
[0131] The first capsule wall, by mass fraction, comprises: 43 parts water glass, 16 parts metakaolin, and 41 parts water;
[0132] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0133] The preparation method of the double-walled microcapsules for cement-based materials in this embodiment is the same as that in Example 1 (when preparing the double-walled microcapsules for cement-based materials in this embodiment, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0134] Comparative Example 1
[0135] The repair materials in this comparative example include:
[0136] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 23 parts sodium bentonite, and 63 parts magnesium oxide-based expanding agent;
[0137] The capsule wall includes a first capsule wall and a second capsule wall;
[0138] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0139] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0140] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0141] Comparative Example 2
[0142] The repair materials in this comparative example include:
[0143] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 23 parts sodium bentonite, and 63 parts calcium sulfoaluminate-based expanding agent;
[0144] The capsule wall includes a first capsule wall and a second capsule wall;
[0145] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0146] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0147] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0148] Comparative Example 3
[0149] The repair materials in this comparative example include:
[0150] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 23 parts sepiolite, and 63 parts calcium oxide expanding agent;
[0151] The capsule wall includes a first capsule wall and a second capsule wall;
[0152] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0153] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0154] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0155] Comparative Example 4
[0156] The repair materials in this comparative example include:
[0157] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 23 parts diatomaceous earth, and 63 parts calcium oxide-based expanding agent;
[0158] The capsule wall includes a first capsule wall and a second capsule wall;
[0159] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0160] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0161] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0162] Comparative Example 5
[0163] The repair materials in this comparative example include:
[0164] The core, by mass, comprises: 14 parts aluminum sulfate octahydrate, 23 parts zeolite, and 63 parts calcium oxide-based expanding agent;
[0165] The capsule wall includes a first capsule wall and a second capsule wall;
[0166] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0167] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0168] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0169] Comparative Example 6
[0170] The repair materials in this comparative example include:
[0171] The core, by weight, comprises: 14 parts of sulfoaluminate cement (strength grade 42.5), 23 parts of sodium-based bentonite, and 63 parts of calcium oxide-based expansive agent;
[0172] The capsule wall includes a first capsule wall and a second capsule wall;
[0173] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0174] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0175] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0176] Comparative Example 7
[0177] The repair materials in this comparative example include:
[0178] The core, by weight, comprises: 14 parts aluminum nitrate, 23 parts sodium bentonite, and 63 parts calcium oxide-based expanding agent;
[0179] The capsule wall includes a first capsule wall and a second capsule wall;
[0180] The first capsule wall, by mass fraction, comprises: 48 parts water glass, 18 parts metakaolin, and 34 parts water;
[0181] The second capsule wall, by mass, comprises: 20 parts of calcium carbonate powder; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0182] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0183] Comparative Example 8
[0184] The repair materials in this comparative example include:
[0185] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 23 parts sodium bentonite, and 63 parts calcium oxide-based expanding agent;
[0186] The capsule wall includes a first capsule wall and a second capsule wall;
[0187] The first capsule wall, by mass parts, comprises: 48 parts silica sol, 18 parts metakaolin, and 34 parts water;
[0188] The second capsule wall, by mass, comprises: 20 parts calcium carbonate; wherein, the first capsule wall is disposed between the capsule core and the second capsule wall.
[0189] The preparation method of the repair material in this comparative example is the same as that in Example 1 (when preparing the repair material in this comparative example, the mass fraction of the core is 300 parts, the mass fraction of the first capsule wall suspension is 80 parts, and the mass fraction of the second capsule wall is 20 parts).
[0190] Comparative Example 9
[0191] The repair materials in this comparative example include:
[0192] The core, by weight, comprises: 14 parts aluminum sulfate octahydrate, 23 parts sodium bentonite, and 63 parts calcium oxide-based expanding agent;
[0193] The capsule wall solution, by mass parts, includes: 48 parts water glass, 18 parts metakaolin, 34 parts water, and 20 parts calcium carbonate powder.
[0194] The preparation method of the repair material in this comparative example includes the following steps:
[0195] (1) Weigh each component according to the stated proportions for later use;
[0196] (2) After mixing 14 parts of aluminum sulfate octadechydrate, 23 parts of sodium bentonite and 63 parts of calcium oxide expansion agent evenly in a mixer at 120±2r / min for 10min, the core powder was agglomerated into balls by spraying anhydrous ethanol (the mass of anhydrous ethanol accounts for 22%±2% of the total mass of the core) in a granulator (speed is 40±5r / min) and dried at 50±2℃ for 2h.
[0197] (3) Mix 38.4 parts of water glass, 14.4 parts of metakaolin and 27.2 parts of water evenly and take the suspension; add 20 parts of calcium carbonate powder to the suspension and mix evenly to make the capsule wall solution.
[0198] (4) The core prepared in step (2) is sieved (with square holes of 1 mm and 3 mm) to obtain core particles with a particle size range of 1-3 mm; the core is then sprayed with the core wall solution obtained in step (3) as the core wall by a spherical granulator; after drying at 60±2℃ for 12 h, it is sieved again to obtain a repair material with a particle size range of 1-3 mm coated with an inorganic core wall (when preparing the repair material of this comparative example, the mass fraction of the core is 300 parts and the mass fraction of the core wall solution is 100 parts).
[0199] Comparative Example 10
[0200] The remediation materials in this comparative example include: 42 parts of aluminum sulfate octahydrate, 69 parts of sodium bentonite, 189 parts of calcium oxide expanding agent, 38.4 parts of water glass, 14.4 parts of metakaolin, 27.2 parts of water, and 20 parts of calcium carbonate (the total mass of aluminum sulfate octahydrate, sodium bentonite, and calcium oxide expanding agent is 300 parts, the total mass of water glass, metakaolin, and water is 80 parts, and the total mass of calcium carbonate is 20 parts).
[0201] The preparation method of the repair material in this comparative example is as follows: After the raw materials are mixed evenly, they are directly poured into a granulator for granulation (the granulation process is the same as in Example 1). After granulation, the material is dried at 60±2℃ for 12 hours to obtain a repair material with a particle size of 1-3mm (ready to be used immediately).
[0202] Experimental Example
[0203] 1. The double-walled microcapsules for cement-based materials in the above embodiment and the repair material of the comparative example were respectively added into the mortar specimens at a mass ratio of 8% to replace standard sand for crack repair rate testing; the mortar specimen mix ratio is shown in Table 2.
[0204] Table 2. Mortar Specimen Mix Proportion / g
[0205]
[0206] Test method: A pressure test was conducted on specimens cured under standard conditions for 7 days, with continuous pressure applied at a rate of 0.6 kN / s. Pressure was immediately stopped when fine cracks began to appear on the surface and inside the specimens. Specimens with crack widths between 0.2 ± 0.05 mm were selected, and the initial crack width was determined using a ZBL-F800 crack comprehensive tester. After that, the cracks were placed in water for a second curing period of 3, 7, and 14 days, and the width of the repaired cracks was measured again. ).
[0207] Crack width healing rate ( Calculate according to formula (3):
[0208] (3)
[0209] In the formula, —Crack width repair rate, %
[0210] —Initial crack width of pre-stressed cracks in specimens cured for 7 days under standard conditions, in mm;
[0211] — Crack widths (mm) after secondary underwater curing for 3, 7, and 14 days.
[0212] The test results are shown in Table 3 below:
[0213] Table 3 Crack width repair rate
[0214]
[0215] As can be seen from the above data, the double-walled microcapsules for cement-based materials in Examples 1-10 of the present invention can significantly improve the crack width repair rate of mortar specimens.
[0216] Based on Example 8 and Comparative Example 1, it can be seen that when Comparative Example 1 uses magnesium oxide expanding agent instead of calcium oxide expanding agent, it cannot provide a sufficient alkaline environment and expanding force in the short time after the crack appears, making it difficult to seal the crack in time and resulting in poor repair effect.
[0217] Combining Example 8 and Comparative Example 2, it can be seen that Comparative Example 2 uses a calcium sulfoaluminate-based expanding agent (the main component of which is anhydrous calcium sulfoaluminate). While calcium sulfoaluminate can react to form ettringite, the core lacks substances that can quickly provide an alkaline environment, thus reducing the efficiency of ettringite formation and affecting the repair effect.
[0218] As can be seen from Example 8 and Comparative Examples 3-5, if porous sepiolite, diatomite, or zeolite is used to replace sodium-based bentonite, although they are all porous minerals, sepiolite, diatomite, or zeolite do not have the property of swelling when exposed to water, resulting in the repair material lacking the ability to physically swell and quickly seal cracks.
[0219] Combining Example 8 and Comparative Example 6, it can be seen that: Comparative Example 6 uses sulfoaluminate cement instead of pure aluminum sulfate octadechydrate. Due to the slow dissolution and reaction rate of sulfoaluminate cement, Al... 3+ and SO4 2- The low release efficiency leads to a reduced efficiency in the formation of ettringite, resulting in poor repair effects on cracks.
[0220] Combining Example 8 and Comparative Example 7, it can be seen that in Comparative Example 7, aluminum nitrate was used instead of aluminum sulfate octadechydrate. Since aluminum nitrate cannot effectively provide SO4... 2- This means that the expansion reaction that produces ettringite will hardly occur; the repair mechanism is only the hydration of calcium oxide to produce calcium hydroxide, resulting in poor repair effect and product density.
[0221] Combining Example 8 and Comparative Example 8, it can be seen that: Comparative Example 8 uses silica sol instead of water glass, but silica sol is mainly composed of nano silica particles, and the content of free silicate ions is much lower than that of water glass. It is difficult to achieve the effect of water glass on rapid activation of metakaolin, resulting in low strength of the first capsule wall. The repair material of this comparative example will crack and release the capsule core prematurely during the mixing process with other components of the mortar specimen, reducing the repair effect on the crack.
[0222] Based on Examples 8 and 9, it can be seen that when calcium carbonate is added to the first capsule wall, the inert calcium carbonate mixes with the active first capsule wall, causing the outermost layer of the capsule wall in Comparative Example 9 to be directly exposed to the alkali-activated components. The alkali-activated material in the capsule wall will react prematurely with the surrounding alkaline mortar specimen, weakening the protective effect on the core functional components inside the repair material and affecting the repair effect on the crack.
[0223] Based on Example 8 and Comparative Example 10, it can be seen that when all raw materials are simply mixed and mixing water is added, a chemical reaction occurs between the raw materials, resulting in the products being randomly distributed in the mortar specimen. In addition, the functional components of the core will also come into direct contact with the mortar specimen and be consumed prematurely, reducing the repair effect on cracks.
[0224] 2. Heat resistance test:
[0225] Test methods: 1) Prepare the capsule core according to the preparation method of the capsule core in Example 1, dry it at 105℃±5℃ for 5-6 hours, then grind it into powder (the residue on a 200-mesh sieve is no more than 5%), and immediately conduct a thermogravimetric test; 2) Spray the first capsule wall suspension in Example 1 onto the glass beads and then coat it with calcium carbonate powder of the second capsule wall. After drying at 105℃±5℃ for 5-6 hours, peel the two capsule walls off the glass beads and grind them into powder (the residue on a 200-mesh sieve is no more than 5%), and immediately conduct a thermogravimetric test.
[0226] The thermogravimetric curves of the core and wall of the double-walled microcapsule for cement-based materials in Example 1 are as follows: Figure 2 As shown; by Figure 2 It can be seen that the mass loss of the core and the wall at a high temperature of 200℃ is less than 5%, which is far lower than that of organic and organic-inorganic composite microcapsules, and is sufficient to withstand the thermodynamic environment of the hydration process of cement-based materials.
[0227] 3. Adhesion performance test:
[0228] After standard curing for 28 days, the mortar specimens containing double-walled microcapsules for cement-based materials from Example 1 were broken and their cross-sections were observed. Figure 3 Cross-sectional view of a mortar specimen with double-walled microcapsules incorporated into Example 1 for cement-based materials, after standard curing for 28 days ((b) is a partial enlarged view of (a)); observation Figure 3 The dark microcapsule outlines and light-colored cores were still clearly visible, and they were tightly bonded and well-adheded to the mortar matrix.
[0229] 4. Compressive strength test
[0230] The compressive strength of the mortar specimens containing the double-walled microcapsules of Example 1 for cement-based materials (the double-walled microcapsules of Example 1 were incorporated into the mortar specimens at a mass ratio of 8% replacement standard sand; the experimental group in Table 2) and the blank group (the blank group in Table 2) were tested after standard curing for 7 days, 14 days, and 28 days. The test results are shown in Table 2. Figure 6 .
[0231] Figure 6 The graph shows the compressive strength test results of mortar specimens with double-walled microcapsules incorporated in Example 1 for cement-based materials and the blank group; from Figure 6It can be seen that the mechanical properties of the mortar specimens with double-walled microcapsules for cement-based materials added in Example 1 decreased slightly compared with the blank group, but the decrease was less than 5%. The double-walled microcapsules for cement-based materials of the present invention help maintain the mechanical properties of the mortar specimens and reduce the negative impact on the mechanical properties of the mortar specimens.
[0232] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A double-walled microcapsule for cement-based materials, characterized in that, include: The core, by mass parts, comprises: 10-30 parts of hydrated aluminum sulfate, 20-40 parts of sodium bentonite, and 50-70 parts of calcium oxide-based expanding agent. The capsule wall includes a first capsule wall and a second capsule wall; The first capsule wall comprises, by mass, 40-50 parts water glass, 15-20 parts metakaolin and 30-45 parts water; The components of the second capsule wall include calcium carbonate; The first capsule wall is disposed between the capsule core and the second capsule wall; The mass ratio of the first capsule wall to the second capsule wall is 4:1; the mass ratio of the core of the double-walled microcapsule for cement-based materials to the sum of the masses of the first and second capsule walls is 3:
1.
2. The double-walled microcapsule for cement-based materials as described in claim 1, characterized in that, The hydrated aluminum sulfate has a fineness of 80-100 mesh and a purity >99wt%. The sodium-based bentonite has a fineness of 600-800 mesh and a total mass content of SiO2 and Al2O3 of ≥85 wt%. The calcium oxide-based expanding agent has a particle size of 200-300 mesh and an effective CaO content of ≥60wt%.
3. The double-walled microcapsule for cement-based materials as described in claim 1, characterized in that, The specific surface area of metakaolin is 11,000-13,000 m². 2 / kg, with a total mass content of SiO2 and Al2O3 ≥97wt%.
4. The double-walled microcapsule for cement-based materials as described in claim 1, characterized in that, The calcium carbonate has a fineness of 6000-8000 mesh.
5. The method for preparing double-walled microcapsules for cement-based materials according to any one of claims 1-4, characterized in that, Includes the following steps: (1) The hydrated aluminum sulfate, sodium bentonite and calcium oxide expansion agent are mixed evenly, granulated and dried to obtain the core; (2) Mix the water glass, metakaolin and water evenly to obtain a suspension; (3) Spray the suspension onto the surface of the capsule core to obtain microcapsules containing a first capsule wall; (4) Calcium carbonate powder is adhered to the surface of the microcapsule containing the first capsule wall obtained by step (3) as the second capsule wall, thus obtaining the double-capsule microcapsule for cement-based materials.
6. The application of the double-walled microcapsules for cement-based materials as described in any one of claims 1-4, characterized in that, The double-walled microcapsules for cement-based materials are used to prepare self-healing cement-based materials.
Citation Information
Patent Citations
Double-layer-capsule wall energy-storage temperature-regulation microcapsule, polyacrylonitrile fiber and preparation methods of double-layer-capsule wall energy-storage temperature-regulation microcapsule andpolyacrylonitrile fiber
CN113913160A
Self-repairing microcapsule as well as preparation method and application thereof
CN120437914A